Architect Herman Bollé and German Neo-Renaissance in Croatian Architecture in the Late 19th Century - Damjanović, Dragan (2013)
In the late 1870s the dominance of the Italian Neo-Renaissance style in Croatian residential and public architecture and the Gothic style in church architecture was superseded by the German Neo-Renaissance style introduced by architect Herman Bollé. Characterized by architectural quality and picturesqueness his German Neo-Renaissance buildings represented a reflection of the European architectural developments in Croatia.
Projekt MZOS
ENG
Keywords: neorenesanasa - -- njemačka neoren. - -- Bollé, Herman - -- Schmidt, Friedrich von - -- Ferstel, Heinrich von - -- Aigner, Alexander von - -- Kršnjavi, Iso - -- Zagreb - -- Marija Bistrica